Eosinophilic Gastroenteritis Presenting as Eosinophilic Ascites: A Rare Clinical Scenario - Shah, Aakash; Bassi, Nitesh; Singh , Pranjal; Parihar, Shishirendu; Mittal, Ishan; Das, Dipankar; Dixit, V. K.; Yadav, D. P. (Medical Research and Its Applications Vol. 5, 2024)
This rare case study highlights eosinophilic gastroenteritis presenting as eosinophilic ascites. Eosinophilic Gastroenteritis (EGE) represents a member of a family of diseases collectively referred to as eosinophilic gastrointestinal disorders (EGIDs) that include eosinophilic esophagitis, gastritis, enteritis, and colitis. The disorder is classified into mucosal, muscular and sub-serosal types. Sub-serosal disease, which is complicated by ascites, is the most severe clinical form of eosinophilic gastroenteritis and requires early corticosteroid therapy. We report a similar case of a 47-year-old male presenting with progressive abdominal distention, who on the investigation was found to be having eosinophilic and low Serum Ascites Albumin Gradient (SAAG) ascites, patient was worked up further with upper and lower GI endoscopies and mucosal biopsies, Cross-sectional imaging, Bone marrow examination and finally diagnosed to be having eosinophilic ascites secondary to Eosinophilic Gastrointestinal Disorders (EGIDs). He was started on steroids in a tapering dose with the Six Food Elimination Diet (SFED) and improved remarkably. The patient is off steroids now and is planning to continue on SFED. The absence of distinctive upper or lower gastrointestinal endoscopic biopsy findings does not rule out the presence of the disease in cases of eosinophilic ascites when there is abdominal discomfort, ascites, and peripheral eosinophilia. Excellent outcomes are achieved with early diagnosis, prompt diagnosis, and oral steroid treatment.